Cd8 enhancer E8(I) and Runx factors regulate CD8α expression in activated CD8(+) T cells - Hassan, Hammad (National Academy of Sciences, 2011)
Cd8a and Cd8b1 coreceptor gene (Cd8) expression is tightly controlled during T-cell development by the activity of five Cd8 enhancers (E8(I)–E8(V)). Here we demonstrate a unique transcriptional program regulating CD8 expression during CD8(+) effector T-cell differentiation. The Cd8 enhancer E8(I) and Runx/core-binding factor-β (CBFβ) complexes were required for the establishment of this regulatory circuit, because E8(I)-, Runx3-, or CBFβ-deficient CD8(+) T cells down-regulated CD8α expression during activation. This finding correlated with enhanced repressive histone marks at the Cd8a promoter in the absence of E8(I), and the down-regulation of CD8α expression could be blocked by treating E8(I)-, Runx3-, or CBFβ-deficient CD8(+) T cells with the histone deacetylase inhibitor trichostatin A. Moreover, Runx/CBFβ complexes bound the Cd8ab gene cluster in activated CD8(+) T cells, suggesting direct control of the Cd8a locus. However, CD8(+) effector T cells maintained high levels of CD8α when CBFβ was conditionally deleted after activation. Thus, our data suggest an E8(I)- and Runx3/CBFβ-dependent epigenetic programming of the Cd8a locus during T-cell activation, leading to Runx/CBFβ complex-independent maintenance of CD8α expression in effector T cells.